(untitled) (Revista Española de Derecho Internacional, 2008)
The forced disappearances of people are the object of the recent 2006 International Convention for the protection of all Persons from Enforced Disappearances, according to which the victims have the right to know the truth, the right to have reparation and an indemnity. This new approach in the International Law of Human Rights has some relevant precedents. The approval by the General Assembly of the Principles on Reparation of the Victims of Human Rights violations is one of them. The other is the Inter-American Court of Human Rights jurisprudence which, thanks to the possibilities opened in article 63 has given details on the reparation duties of the States towards the victims of human rights violations. Concerning reparation, the International Law of human rights differs from the customary rules on international responsibility law for wrongful acts of States as the most important focus is on the individual and not on State sovereignty. The role that satisfaction plays as a way of reparation is very large. The Spanish Act for historical memory had to respond to the requirements of the Civil War enforced disappearances victims. However the law contains some deficiencies as for the protection of the victims according to international standards.